Process modeling of a reversible solid oxide cell (r-SOC) energy storage system utilizing commercially available SOC reactor. (15th June 2017) - Mottaghizadeh, Pegah; Santhanam, Srikanth; Heddrich, Marc P.; Friedrich, K. Andreas; Rinaldi, Fabio
Highlights: An electric energy storage system was developed based on a commercially available SOC reactor. Heat generated in SOFC mode of r-SOC is utilized in SOEC operation of r-SOC using latent heat storage. A round trip efficiency of 54.3% was reached for the reference system at atmospheric pressure. An improved process system design achieved a round-trip efficiency of 60.4% at 25 bar. Abstract: The increase of intermittent renewable energy contribution in power grids has urged us to seek means for temporal decoupling of electricity production and consumption. A reversible solid oxide cell (r-SOC) enables storage of surplus electricity through electrochemical reactions when it is in electrolysis mode. The reserved energy in form of chemical compounds is then converted to electricity when the cell operates as a fuel cell. A process system model was implemented using Aspen Plus® V8.8 based on a commercially available r-SOC reactor experimentally characterized at DLR. In this study a complete self-sustaining system configuration is designed by optimal thermal integration and balance of plant. Under reference conditions a round trip efficiency of 54.3% was achieved. Generated heat in fuel cell mode is exploited by latent heat storage tanks to enable endothermic operation of reactor in its electrolysis mode. In total, out of 100 units of thermal energy stored in heat storage tanks during fuel cell mode, 90% was utilized to offset heat demand of system in its electrolysis mode. Parametric analysis revealed the significance of heat storage tanks in thermal management even when reactor entered its exothermic mode of electrolysis. An improved process system design demonstrates a system round-trip efficiency of 60.4% at 25 bar.